Agronegocios sudamericanos: Un análisis de la comercialización de productos agrícolas entre el Mercosur y la Unión Europea (Research, Society and Development, 2021)
This work aims to analyze the trade in agricultural products between Mercosur and the European Union. Through the bibliographic study it was possible to verify the international commercial relations until the elaboration of the agreement between Mercosur and the European Union. The general objective of the study was to analyze the evolution of trade in agricultural products between Mercosur and the European Union between 2009 and 2019 and to analyze the trade agreement between the two economic blocs. The adopted methodology was the Bibliographic Review from the main authors of the area, followed by an illustrative example from the literature. The research enabled some considerations and reflections on the theme, such as: from the free trade agreement, MERCOSUR has a chance to expand its agribusiness at a level of global importance, but some infrastructure problems must be overcome, to add agility to the process logistics of product distribution; when evaluating the commercial integration between Mercosur and the European Union for agricultural products, it is possible to conclude that the European Union is the main buyer of the agricultural inputs of Mercosur and that this free trade agreement will expand this market in a differentiated way, making the countries members of Mercosur, the largest agricultural producers on the planet.